Cultural and Historical Aspects in Developing the System of Accounting - Kovaleva, Valentina Danilovna; Rusetskiy, Mikhail Gennad’evich; Efremova, Lyudmila Anatolyevna; Kalakhanova, Zukhra Mukhtarovna; Kochkarova, Zarema Ruslanovna (Journal of History Culture and Art Research, 2018)
The article considers historical stages in the development of accounting as a part of the world culture. The specific features of each stage of evolution are represented and the main aspects of accounting information system as a source of relevant data are identified. The effectiveness of the controlling toolkit to improve the system of accounting is substantiated, the main provisions of the controlling conception are singled out and generalised; the scientific schools and their differences are identified. The analysis of various definitions revealing the content of the notion "culture" based on the condition and achievements of society as a collective of individuals who are in turn characterised by the unity of social, economic and cultural life is carried out. The essence of the notion "culture" and its versatility are determined; the actions of individuals responsible for the evolution of the economic life of society as a reaction to the obtained information are substantiated. The necessity to reflect the main provisions of accounting from the standpoint of their influence on economic decision-making, individuals’ consciousness, distribution of resources, trajectory of economic development and the well-being of economic entity is investigated. The necessity to represent accounting as a subsystem of culture is substantiated. The main definitions of the notion "culture" which are most appropriate for characterising the subject matter of accounting are studied. The key aspects of describing the system of accounting as a culture component are identified.